Mineral Composition of Clay Fraction of the Chernozems Spread out in Ovče Pole in Republic of Macedonia - Mile MARKOSKI, Tatjana MITKOVA, Vedran RUBINIĆ (Agriculturae Conspectus Scientifi cus | Vol. 76 (2011) No. 1 (71-75), 2011)
Th e results of mineral composition of the clay fraction of the chernozems spread out in Ovče Pole are presented. Th e mechanical composition of the soil samples show high domination of the physical clay and clay fractions in the soil separates, what is one of the reasons for strong infl uence on the physical and physical-mechanical prop erties of the soil. Th e clay content is dominant in the soil separates fraction and var ies from 23.60% to 56.90%, or 36.23% average. Th e average content of physical sand and physical clay fractions is 42.20% and 57.80% respectively. Analysis of the mineral composition of clay in its entirety showed that no one of the minerals in the analyzed chernozem samples is not in absolute domination, but there is evident higher presence of clay minerals with 2:1 lattice type (vermiculite, illite and smectites) in comparison with 1:1 lattice type (kaolinite). Th is shows that our variety of vertical chernozems has little deteriorated physical and physical-mechanical properties compared with typical chernozems.
Keywords: chernozems, mineral composition, clay, physical-mechanical properties